Web-Based Village Land Information System Development for Optimizing Regional Land Administration - Sidiq, Habibi Hasbi; Junarto, Rohmat; Wahyuni, Wahyuni (Indonesian Scientific Journal, 2025)
Access to land information in Indonesia is restricted, especially at the village and sub-district levels, where detailed data is essential for efficient land administration. This research aims to create a web-based Village Land Information System to improve regional land administration through the provision of organized, accessible, and dependable land data. The study employed a Research and Development (R&D) methodology using a prototyping approach, gathering data through observation, surveys, and literature analysis. Data were examined using both descriptive and quantitative methods, with validation and reliability assessments conducted on questionnaires administered to 100 respondents. The assessment employed the End User Computing Satisfaction (EUCS) and Importance-Performance Analysis (IPA) methodologies. The system development encompassed multiple phases: requirements analysis, prototype design, implementation, functionality testing, and evaluation. The Unified Modeling Language (UML) was utilized for system modeling, and user interfaces were crafted with a focus on usability. Functionality tests verified that all features functioned well, and user assessments revealed significant satisfaction with the system’s content, correctness, format, usability, and promptness. The application markedly enhanced land administration by providing comprehensive land information, facilitating access, elucidating service procedures, and systematizing data storage. The results illustrate the capability of web-based technologies to enhance regional land administration and facilitate village government in improving service delivery and land information management.